Gamifying Education: Exploring Student Perceptions of Kahoot! As a Learning Medium - Oktaviani, Anggit Laesa (STAIRS: English Language Education Journal, 2024)
This study investigates students' perceptions of Kahoot! as a learning medium for English at Sekolah Tinggi Bahasa Asing Technocrat. Employing a qualitative approach, the research gathers data through questionnaires, interviews, and observations. The sample includes 37 students from various academic years who have utilized Kahoot! in both online and offline English classes. The findings indicate a generally positive perception of Kahoot!. Based on the questionnaire results, 47.78% of students demonstrated high motivation to learn English using Kahoot!, attributing this to its competitive features and engaging atmosphere. Students expressed a preference for Kahoot! exercises over traditional textbooks, highlighting the scoring system as particularly motivating. Regarding material comprehension and skill development, 47.98% agreed that Kahoot! enhances their understanding of English materials and improves their language skills. Additionally, students reported that Kahoot! supports material review, fosters supplementary learning, and strengthens vocabulary retention. In terms of the learning process, 64% of respondents agreed that Kahoot! facilitates effective learning by encouraging group collaboration, increasing classroom interaction, and improving material retention compared to conventional teaching methods. Overall, the study concludes that Kahoot! is an effective and engaging tool for teaching and learning English at the tertiary level.